Imaging and Analysis of Encapsulated Objects through Self‐Assembled Electron and Optically Transparent Graphene Oxide Membranes. Issue 2 (1st December 2016) - Yulaev, Alexander; Lipatov, Alexey; Lu, Annie Xi; Sinitskii, Alexander; Leite, Marina S.; Kolmakov, Andrei
Abstract : This study demonstrates a technique for facile encapsulation and adhesion of micro‐ and nanoobjects on arbitrary substrates, stencils, and microstructured surfaces by ultrathin graphene oxide membranes via a simple drop casting of graphene oxide solution. A self‐assembled encapsulating membrane forms during the drying process at the liquid–air and liquid–solid interfaces and consists of a water‐permeable quasi‐2D network of overlapping graphene oxide flakes. Upon drying and interlocking between the flakes, the encapsulating coating around the object becomes mechanically robust, chemically protective, and yet highly transparent to electrons and photons in a wide energy range, enabling microscopic and spectroscopic access to encapsulated objects. The characteristic encapsulation scenarios have been demonstrated on a set of representative inorganic and organic micro‐ and nanoobjects and microstructured surfaces. Different coating regimes can be achieved by controlling the pH of the supporting solution, and the hydrophobicity and morphology of interfaces. Several specific phenomena, such as compression of encased objects by contracting membranes as well as hierarchical encapsulations, have been observed. Finally, electron/optical microscopy, analysis of encapsulated objects, and the effect of membrane on the image contrast formation and signal attenuation are discussed. Abstract : This study demonstrates a facile drop‐casting technique for encapsulation and adhesion of micro‐ and nanoobjects on arbitrary substrates, stencils, and microstructured surfaces by ultrathin graphene oxide membranes. Such membranes are mechanically robust, chemically protective, and yet highly transparent to electrons and photons. Thus, the membranes enable electron/optical microscopy and spectroscopy to be performed on encapsulated objects.